TARPs Modulate Receptor-Mediated Paired-Pulse Depression and Recovery from Desensitization - Devi, Suma Priya Sudarsana (J Neurosci, 2020)
Transmembrane AMPA receptor regulatory proteins (TARPs) are auxiliary AMPA receptor subunits that play a key role in receptor trafficking and in modulating receptor gating. The ability of TARPs to slow both deactivation and desensitization is isoform specific. However, TARP isoform-specific modulation of receptor properties remains uncharacterized. Here, we compare the isoform-specific effects of γ–2, γ–3, γ–4, and γ–8 TARPs on recovery from desensitization and responses to pairs of brief applications of glutamate. All four isoforms were able to reduce receptor-mediated paired-pulse depression and significantly speed recovery from desensitization in an isoform-specific manner. In the presence of TARPs, recovery time courses were observed to contain two components, fast and slow. The proportion of fast and slow components was determined by the TARP isoform. The time constant of recovery was also altered by the duration of glutamate application. When studies with TARP chimeras were performed, TARP extracellular loops were found to play a vital role in TARP modulation of recovery. Thus, isoform-specific differences in TARP modulation of recovery from desensitization influence receptor responses to repeated brief applications of glutamate, and these differences may impact frequency-dependent synaptic signaling in the mammalian central nervous system. SIGNIFICANCE STATEMENT AMPA receptors are major determinants of excitatory synaptic strength. The channel kinetics of AMPA receptors contribute to the kinetics of synaptic transmission. Transmembrane AMPA receptor regulatory proteins (TARPs) auxiliary subunits can modulate the decay kinetics of AMPA receptors. However, whether TARP isoforms specifically modulate receptor recovery is unclear. Here, we investigated the recovery kinetics of AMPA receptors by expressing various TARP isoforms and chimeras. We observed that the TARP isoforms and duration of glutamate application uniquely modulate time constants and the proportion of fast and slow components through a previously unidentified TARP domain. Given the impact of recovery kinetics on receptor responses to repetitive stimulation such as synaptic transmission, this work will be of great interest in the field of excitatory synaptic transmission research.